Dermatological Manifestations in Diabetes Mellitus at NGMCTH Kohalpur - Pandey, Sumit; Mishra, Pradip; Sharma, Nirmala; B.K., Shyam (Journal of Nepalgunj Medical College, 2017)
Background: Skin is the largest and most visible organ in the body. It undoubtedly determines to a great extent our appearance and plays a major role in socio-sexual communication. More than one third of diabetic patients have some type of dermatologic 1 manifestations during the course of their chronic disease . The association of certain skin diseases with diabetes mellitus has been 2 3 fairly well recognized with an incidence rate ranging from 11.4% to 66%. At least 30% of patients with diabetes mellitus have some 4 5 type of cutaneous involvement during the course of their chronic disease. Skin sugar levels run parallel to the blood sugar levels. Skin changes generally appear subsequent to the development of DM but may be the first presenting sign or even precede the 6 diagnosis by many years. Among the many skin manifestations in DM, none is pathognomonic of this disease. Cutaneous findings in DM can be classified into four categories: (1) skin disease with strong association and others with less distinct association with DM, (2) cutaneous infections, (3) dermatological disorders related to diabetic complications, and (4) skin conditions related to diabetes 7 treatments. Objectives: This study was undertaken to find out the pattern of Dermatological manifestations in Diabetes patients attending Nepalgunj Medical College Teaching Hospital, Kohalpur. Method and material: This is a hospital- based descriptive study conducted in the Department of Dermatology, Venereology and Leprology of Nepalgunj Medical College Teaching Hospital, Kohalpur between September 2013 to August 2014. A total of 100 patients were included in the study. History and clinical examinations were performed and the data were recorded and analyzed. Results: The age of the patients ranged from 20 years to 85 years with the mean age of 51.7+12.13 years. The most common age groups were 46-55 years (36%) followed by 56-65 years (24.7%) and 36-45 years (17.3%), 66-75 years (9.3%), 76-85 years (12.7%). Among the 100 patients of diabetes ellitus, there were 44(44%) males and 56 (56%) females. Among the cutaneous disorders commonly associated with diabetes, infections were the most prevalent. 59(59%) out of 100 patients had skin infections. Conclusions: Patients with Diabetes can present with array of cutaneous disorders. Cutaneous infections formed the largest group of dermatoses in this study. Increased incidence of cutaneous infections mainly fungal and bacterial was noticed in majority diabetics emphasizing the need for more aggressive management of diabetes mellitus. Among infective dermatoses, fungal infections were the most common, with Candidal infections being more common than dermatophytosis. JNGMC Vol. 13 No. 2 December 2015, Page: 31-34